Teaching-learning process and the attitude toward scientific research among midwifery students - John Barja-Ore; Willy Ramos; Jhony A. De La Cruz Vargas; Rudi Amalia Loli Ponce (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Research in universities requires systematic and participatory processes that integrate teachers, contents, strategies and tools, and students and their own interests. Therefore, the main objective of this study was to establish the relationship between the perception of the teaching-learning process (TLP) and the attitude toward scientific research among midwifery students. MATERIALS AND METHODS: Descriptive cross-sectional study, conducted on 250 students from second to fourth year of study selected by convenience sampling. The data were collected with two self-administered Likert-type scales that were validated in content and construct, both with high reliability. Descriptive statistics were carried out; the Spearman correlation test was used prior to the application of the Kolmogorov-Smirnov test and Kendall's tau-b test. RESULTS: The favorable perception of the TLP was greater among second-year students (42.6%), in addition, 15.2% agreed that the advice of teachers contributes to the elaboration of the research protocol. The attitude of indifference toward research was more frequent in third-year students (58.2%) and 28.4% were deemed in disagreement to be able to identify and operationalize the variables. In the analysis of dimensions, the role of the student had a moderate relationship with the research design (rho = 0.536; P < 0.001), while a weak relationship was demonstrated between media and techniques with ethical and scientific value (rho = 0.104; P < 0.001). CONCLUSION: The TLP perceived by midwifery students and their attitudes toward scientific research had a direct and significant correlation. The proportion of students with favorable perception was greater among those with a favorable attitude.